Acidic Barren Slope Profiling using Electrical Resistivity Imaging (ERI) at Ayer Hitam area Johor, Malaysia - Azhar A.T.S.; Hazreek Z.A.M.; Aziman M.; Haimi D.S.; Hafiz Z.M. (Institute of Physics Publishing, 2023)
Data acquisition; Imaging techniques; Mapping; Nondestructive examination; Probes; Soils; Sustainable development; Electrical resistivity imaging; Electrical resistivity imaging (ERI); Environmental sustainability; Field data acquisition; Knowledge constraints; Nondestructive methods; Resistivity values; Subsurface profile; Electric conductivity